KREATIVITAS GURU MENGGUNAKAN MODEL PEMBELAJARAN DALAM MENINGKATKAN HASIL BELAJAR SISWA - ABIDIN, ANDI MUSTIKA (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2017)
This research shows that the importance of the teacher creativity through learning style in improving the student’s performance learning outcomes.The teacher as profesionals in the field of education, in addition to understand philosophical and conceptual matters, and to know and implement technical matters. There are some technical matters especially the activity of managing and implementing of teaching and learning interaction. In the managing activity of teaching and learning interaction, the teacher as much as possible to facilitate the students to gain the learning experienc. It can be realized with the creativity of teachers (held a variety of teaching and use media) in using the model of learning, so that with the creativity of teachers can improve student learning outcomes.